Dietary Quality and Body Composition on Lipid Profile in Endurance Athletes Aged 13-18 Years in Central Java Province - Mardiana, Mardiana; Safrina Oksidriyani; Farida Dwi Rokhmah; Safira Chairani Dimarti; Rsyad, Ula Saza Bayli; Faizin, Miftahul; Nareswara, Anastu Regita (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2025)
Diet quality and body composition are critical determinants of lipid metabolism and cardiovascular health in adolescent athletes. However, the relationship between these factors and lipid profiles in this population remains underexplored. This study aimed to examine the association between anthropometric indicators, diet quality, and lipid profile parameters in adolescent athletes. A cross-sectional study was conducted on 72 adolescent athletes. Univariate analysis described participants’ characteristics, including anthropometric measures, diet quality using the Alternative Healthy Eating Index (AHEI), blood pressure, lipid profiles, and physical activity levels. Data normality was tested using the Kolmogorov–Smirnov test. Pearson or Spearman correlation tests were applied for bivariate analysis, and logistic regression was used for multivariate analysis. Statistical significance was set at p < 0.05. Participants had a mean BMI of 21.9 ± 2.1 kg/m², body fat percentage of 19.3 ± 5.5%, and AHEI score of 51.1 ± 10.6, indicating moderate diet quality. Most lipid parameters were within normal ranges. Bivariate analysis revealed no significant associations between BMI, waist circumference, or AHEI score with lipid parameters. Waist-to-hip ratio was positively associated with HDL (p = 0.017). Body fat percentage showed significant associations with total cholesterol (p = 0.001), HDL (p = 0.001), LDL (p = 0.007), and triglycerides (p = 0.010). Multivariate analysis confirmed body fat percentage as the strongest predictor of lipid profile alterations. Body fat percentage is a more sensitive indicator of lipid metabolism changes than BMI in adolescent athletes.